Clinical characteristics and elevated ProGRP and positive oligoclonal bands of 13 Chinese cases with anti‐GABABR encephalitis. Issue 6 (22nd May 2021) - Wu, Huaikuan; Wang, Yuliang; Wei, Kunkun; Qiao, Shan; Liu, Lingling; Zhang, Ranran; Cao, Lili; Wang, Shengjun; Liu, Xuewu
Abstract: Objective: To improve the clinical understanding of anti‐gamma‐aminobutyric‐acid B receptor encephalitis (anti‐GABABR encephalitis) by analyzing 13 cases. Methods: We retrospectively studied demographic and clinical features including clinical symptoms, serum/cerebrospinal fluid (CSF) laboratory findings (including antibody test), brain magnetic resonance imaging (MRI), electroencephalogram (EEG), treatment plan, and treatment effect for 13 patients with a definitive diagnosis of anti‐GABABR encephalitis. Results: Seven patients (53.8%, 7/13) were complicated with lung cancer. Epileptic seizures were the most common symptoms at onset in 11 patients (84.6%, 11/13). All patients had seizures in the course of the disease. Abnormalities in craniocerebral MRI examination, including hippocampus, occipital lobe, insular lobe, were found in six of nine tested patients, and EEG abnormalities were found in seven out of nine tested patients. Elevated pro‐gastrin releasing peptide (ProGRP) levels were found in 70% of patients with a median value of 490.10 pg/ml; and CSF oligoclonal bands were positive for 4 of 10 tested cases. However, there were no significant differences in modified Rankin Scale (mRS) between the ProGRP or CSF oligoclonal band positive and negative groups at admission and follow‐up ( p > .05). The value between SCLC and non‐SCLC subgroup was significantly different ( p < .05). Ten patients received immunotherapy (three patients refused treatment). After immunotherapy, the frequency of seizures was significantly reduced. There was a significant difference in mRS between admission and after treatment ( p < .05). The average survival time after onset was 27.7 months. Conclusions: Epilepsy is the most common clinical manifestation of Anti‐GABABR encephalitis. The prognosis of anti‐GABABR encephalitis is poor. Section of anti‐GABABR encephalitis patients have higher level of serum ProGRP and positive GSF oligoclonal bands. Elevated ProGRP or positive CSF oligoclonal bands with classic clinical features can potentially help to improve early recognition of anti‐GABABR encephalitis. Abstract : Seven patients (53.8%, 7/13) were complicated with lung cancer. The prognosis of anti‐GABABR encephalitis is poor. Section of anti‐GABABR encephalitis patients have higher level of serum ProGRP and positive GSF oligoclonal bands. Elevated ProGRP or positive CSF oligoclonal bands with classic clinical features can potentially help to improve early recognition of anti‐GABABR encephalitis.